Analisis Bioinformatika Ekspresi MIER3 sebagai Biomarker Potensial dan Target Terapeutik pada Kanker Esofagus - Amukti, Danang; Ria Indah Pratami (JURNAL FARMASI GALENIKA, 2025)
Esophageal cancer (ESCA) is one of the cancers with high mortality rates worldwide. Determination of prognostic biomarkers that can predict patient survival is very important to support more effective therapy management. The MIER3 gene has been reported to play a role in the regulation of gene expression and cell proliferation pathways, but its role in ESCA is still not fully understood. MIER3 gene expression data and patient clinical information were obtained from the UALCAN database based on TCGA. Survival analysis was performed using the Kaplan-Meier method to evaluate the effect of MIER3 expression levels on ESCA patient survival. Further analysis was performed by combining MIER3 expression with clinical variables such as tumor grade, race, gender, and weight status. MIER3 expression was significantly higher in tumor tissue than in normal tissue. Kaplan-Meier showed that patients with high MIER3 expression had significantly lower survival than the low expression group (p = 0.00013). The combination of MIER3 expression and clinical factors such as gender (p = 0.00046), race (p = 0.0095), and body weight (p = 0.008) also showed a prognostic relationship to survival. MIER3 has the potential as a prognostic biomarker in esophageal cancer. High MIER3 expression correlates with poor prognosis, especially when combined with certain clinical factors. These findings suggest that MIER3 may play a role in tumor progression through molecular mechanisms involving activation of proliferative pathways and inhibition of apoptotic pathways, and support the development of gene expression-based targeted therapy.